Medicinal pteridophytes of sitheri hills, eastern ghats, tamil nadu - D, Moorthy; T, Kavitha (Kongunadu Research Journal, 2020)
Investigation on medicinal properties and nutritional values of higher plants were commonly reported but often neglected the pteridophytes. Despite the rich flora in and around Sitheri, study on their medicinal uses were limited. The objective of the investigation is to document of medicinal pteridophytes,in sitheri hills.